ANALISIS KEPUASAN KONSUMEN YANG DIPENGARUHI OLEH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN PERSEPSI HARGA - Fanny Putri Anggraini; Aris Budiono (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
This research is directed to see whether there is a simultaneous or partial relationship between Product Quality (X1), Service Quality (X2) and Perceived Price (X3) on Consumer Satisfaction (Y). The validity and reliability of the survey were evaluated by including one hundred and thirty respondents. To ascertain whether there is a partial or simultaneous effect, we use the SPSS 24 quantitative method software with multiple linear regression. based on the conclusion that product quality, service quality, and price perceptions are all influenced simultaneously by these three independent variables. Product quality and service quality are two independent variables which partially have no effect on the dependent variable. However, consumer satisfaction is influenced by price perception variables